2021
DOI: 10.1080/19942060.2021.1974091
|View full text |Cite
|
Sign up to set email alerts
|

Simulation strategy of the full-scale ship resistance and propulsion performance

Abstract: The ship powering performance can be predicted based on model tests or simulations. However, differences exist between the full-scale ship performance and extrapolated model data. Therefore, research on full-scale ship performance simulation has important scientific significance and engineering value. This study used the REGAL general cargo vessel to perform full-scale ship resistance and self-propulsion simulations for various grid numbers, time step sizes, and wall Y+ values and compared the calculation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The sensitivity analysis to mitigate the effects of domain boundaries on the flow near the hull confirmed that a computational domain with dimensions of 180 m (y-direction), 30 m (x-direction) and 45 m (z-direction) is suitable. The upstream and downstream of the ship are assumed to be 1 and 2 times the length of the ship (L Ship ), respectively, which is consistent with the previous studies [21]. The water depth is determined by adding 30 m to the ship's draught (30 m + h Draught ).…”
Section: Problem Statementmentioning
confidence: 98%
“…The sensitivity analysis to mitigate the effects of domain boundaries on the flow near the hull confirmed that a computational domain with dimensions of 180 m (y-direction), 30 m (x-direction) and 45 m (z-direction) is suitable. The upstream and downstream of the ship are assumed to be 1 and 2 times the length of the ship (L Ship ), respectively, which is consistent with the previous studies [21]. The water depth is determined by adding 30 m to the ship's draught (30 m + h Draught ).…”
Section: Problem Statementmentioning
confidence: 98%
“…In this study, the average wall y+ value was set to below 2.5 for the model-scale simulations, according to the ITTC recommendations [10], and to 100-200 for the full-scale simulations (this range of values has been proven to be suiTable for full-scale simulations in many studies [11] [12] [13] [14]). The time step for the URANS simulations depends on the properties of the flow [15].…”
Section: Numerical Setupmentioning
confidence: 99%
“…It is used to ensure the closure equation and has been proven in numerous studies on the hydrodynamic predictions of RDT [16][17][18] and traditional propellers. [19][20][21][22] The transport equations for k and x are as follows:…”
Section: Numerical Details a Governing Equations And Turbulence Modelmentioning
confidence: 99%